2018
DOI: 10.1016/j.tiv.2017.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological effects of regulated mycotoxins and persistent organochloride pesticides: In vitro cytotoxic assessment of single and defined mixtures on MA-10 murine Leydig cell line

Abstract: Epidemiological studies show that there is global decline in male fertility primarily as a result of poor sperm quality and this is attributed to exposure to endocrine disrupting chemicals (EDCs) in the environment, food and pharmaceutical products, including mycotoxins and pesticides. The Leydig cells in the male testes are responsible for producing androgens, hormones that play major roles in male development and reproductive function. Therefore, any toxin that affects the function and morphology of the Leyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 103 publications
0
17
0
Order By: Relevance
“…The mechanisms through which mycotoxin mixtures can impact on testicular morphology and steroidogenesis also deserves attention. In a previous study, we have shown that DON, α-ZOL and OTA were strongly cytotoxic to MA-10 Leydig cells in vitro after 48 h of exposure (Eze et al, 2018). In the same study, OTA did not induce much cytotoxicity up to 16 μM when cells were treated with only this compound, but co-exposure of OTA with DON increased the cytotoxicity at 8-32 μM compared to DON or OTA alone.…”
Section: Mycotoxin Co-exposure and Implication For Human Reproductivementioning
confidence: 72%
See 2 more Smart Citations
“…The mechanisms through which mycotoxin mixtures can impact on testicular morphology and steroidogenesis also deserves attention. In a previous study, we have shown that DON, α-ZOL and OTA were strongly cytotoxic to MA-10 Leydig cells in vitro after 48 h of exposure (Eze et al, 2018). In the same study, OTA did not induce much cytotoxicity up to 16 μM when cells were treated with only this compound, but co-exposure of OTA with DON increased the cytotoxicity at 8-32 μM compared to DON or OTA alone.…”
Section: Mycotoxin Co-exposure and Implication For Human Reproductivementioning
confidence: 72%
“…This is supported by an in vitro study in which exposure of MA-10 murine Leydig cell line to DON increased the release of reactive oxygen species, significantly reduced cell viability and caused significant decline in forskolin-induced progesterone secretion after 24 h of exposure (Savard et al, 2016). In a more recent study, we showed that DON was strongly cytotoxic to MA-10 cells after 48 h of exposure with concentrations as low as 29.63 ng/ml (0.1 µM) and 296.32 ng/ml (1 µM) showing significant cytotoxicity (Eze et al, 2018). Urinary concentrations of 436 ng/ml (1.471 µM) and 1,238 ng/ml (4.178 µM) have been reported for DON and its conjugates in pregnant women (Sarkanj et al, 2013;Wells et al, 2016) and therefore, the concentrations causing cytotoxic effects on MA-10 cells have clinical relevance.…”
Section: Reproductive and Developmental Health Effects Of Deoxynivalementioning
confidence: 86%
See 1 more Smart Citation
“…Indeed, epidemiological studies suggest an association between exposure to pesticides and semen quality ( Swan et al., 2003 ). In that respect, the global decline in male fertility is mainly attributed to the exposure of spermatozoa to environmental EDCs, pharmaceutical products, pesticides and mycotoxins of food origin ( Eze et al., 2018 ; Mann et al., 2020 ; Tavares et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, environmental toxicant exposure has increased throughout the world, leads to infertility, reduced sperm quality, and male reproductive system abnormalities, and has attracted global attention [13]. The continued decline in male fertility was multifactorial, in part result from the exposure to mycotoxins [14]. As widely occurring natural pollution, T-2 toxin was widely distributed in various crops and could infect humans and animals through various pathways [1].…”
Section: Introductionmentioning
confidence: 99%